Reflections on the presence of women in classical music in Peru - Maggiolo Dibos, Mina (2021)
Starting as one of the main channels of primitive human communication, music has always been linked to the existence of man. In this article, we will try to make some reflections where we can follow, in a general way, how women relate to music in a timeline through history, according to its progressive prominence in public space. Finally, we will name some of the outstanding female representatives in the musical field of Peru during the period between the 20th and 21st centuries